Influence of ceramic surface conditioning and resin cements on microtensile bond strength to a glass ceramic - Pisani-Proenca, Jatyr; Erhardt, Maria Carolina G.; Valandro, Luiz Felipe; Gutierrez-Aceves, Guillermo; Bolanos-Carmona, Maria Victoria; Del Castillo-Salmeron, Ramon; Bottino, Marco Antonio (Elsevier B.V., 2006)
Statement of problem. It is not clear how different glass ceramic surface pretreatments influence the bonding capacity of various luting agents to these surfaces.Purpose. The purpose of this study was to evaluate the microtensile bond strength (mu TBS) of 3 resin cements to a lithia disilicate-based ceramic submitted to 2 surface conditioning treatments.Material and methods. Eighteen 5 X 6 X 8-mm ceramic (IPS Empress 2) blocks were fabricated according to manufacturer's instructions and duplicated in composite resin (Tetric Ceram). Ceramic blocks were polished and divided into 2 groups (n=9/treatment): no conditioning (no-conditioning/control), or 5% hydrofluoric acid etching for 20 seconds and silanization for 1 minute (HF + SIL). Ceramic blocks were cemented to the composite resin blocks with I self-adhesive universal resin cement (RelyX Unicem) or 1 of 2 resin-based luting agents (Multilink or Panavia F), according to the manufacturer's instructions. The composite resin-ceramic blocks were stored in humidity at 37 degrees C for 7 days and serially sectioned to produce 25 beam specimens per group with a 1.0-mm(2) cross-sectional area. Specimens were thermal cycled (5000 cycles, 5 degrees C-55 degrees C) and tested in tension at 1 mm/min. Microtensile bond strength data (MPa) were analyzed by 2-way analysis of variance and Tukey multiple comparisons tests (alpha=.05). Fractured specimens were examined with a stereomicroscope (X40) and classified as adhesive, mixed, or cohesive.Results. The surface conditioning factor was significant (HF+SIL > no-conditioning) (P<.0001). Considering the unconditioned groups, the mu TBS of RelyX Unicem was significantly higher (9.6 +/- 1.9) than that of Multilink (6.2 +/- 1.2) and Panavia F (7.4 +/- 1.9). Previous etching and silanization yielded statistically higher mu TBS values for RelyX Unicem (18.8 +/- 3.5) and Multilink (17.4 +/- 3.0) when compared to Panavia F (15.7 +/- 3.8). Spontaneous debonding after thermal cycling was detected when luting agents were applied to untreated ceramic surfaces.Conclusion. Etching and silanization treatments appear to be crucial for resin bonding to a lithia disilicate-based ceramic, regardless of the resin cement used.